2002
DOI: 10.1038/sj.onc.1205581
|View full text |Cite
|
Sign up to set email alerts
|

The expression of DNA methyltransferases and methyl-CpG-binding proteins is not associated with the methylation status of p14ARF, p16INK4a and RASSF1A in human lung cancer cell lines

Abstract: Promoter hypermethylation is an important means for the transcriptional repression of a number of cancerassociated genes. However, the underlying mechanism of this aberration in cancer remains unclear. Here, we examined 5' CpG island methylation status and expression of the p14 ARF , p16 INK4a and RASSF1A tumor suppressor genes, and investigated the relationship of these factors with the mRNA expression of DNA methyltransferases (DNMTs) and/or methyl-CpG-binding proteins (MBPs) in 30 lung cancer cell lines inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 40 publications
4
60
0
1
Order By: Relevance
“…These findings suggest that DNMT1 hypermethylates survival-associated tumour suppressor genes, leading to their functional inactivation. However, a recent report (Sato et al, 2002) found no significant association between DNMT1 expression and DNA methylation of some tumour-associated genes, suggesting that DNMT1 also contributes to cancer development and progression through alternative pathways. For example, Number of patients may not add up to the total number due to assay failure.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These findings suggest that DNMT1 hypermethylates survival-associated tumour suppressor genes, leading to their functional inactivation. However, a recent report (Sato et al, 2002) found no significant association between DNMT1 expression and DNA methylation of some tumour-associated genes, suggesting that DNMT1 also contributes to cancer development and progression through alternative pathways. For example, Number of patients may not add up to the total number due to assay failure.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, new prognostic markers are needed to help identify patients with poor prognoses, who may benefit from more aggressive treatment approaches. Previous studies have consistently reported that DNMT isoforms are significantly upregulated in human lung cancer cell lines and NSCLC tissue specimens (Sato et al, 2002;Vallbohmer et al, 2006). However, studies of the association between DNMT expression and clinical outcome in NSCLC patients have produced inconsistent results (Kim et al, 2006;Vallbohmer et al, 2006;Lin et al, 2007), and few have evaluated the prognostic value of MBD2.…”
mentioning
confidence: 99%
“…Deregulation of DNA methyltransferases have been implicated as a potential link to hypermethylation [54]. Some studies suggest that the activity of DNA methyltransferases does not correlate with the hypermethylation of CpGs within a gene [55] yet, others have shown elevated DNA methyltransferases in a subset of patients which exhibit gene hypermethylation [53,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] However, other reports suggest that DNMT overexpression does not by itself seem to sufficiently account for the hypermethylation of TSG promoters. 19,21,23,24 UHRF1 (also known as ICBP90) has recently been shown to play an important role in methylation maintenance. 25 It has the ability to bind hemimethylated DNA through its SET-and RING-associated domain, 26,27 triggering the recruitment of DNMT1 25,28 and histone deacetylace-1.…”
mentioning
confidence: 99%